Effect of Cigarette Smoke Exposure Status on Pregnant Women as Passive Smokers with Birth Weight in Arjasa Health Center, Jember Regency - Anis Talitha Damarawati; Dwita Aryadina Rachmawati; Hairrudin Hairrudin (Journal of Agromedicine and Medical Sciences, 2020)
In Indonesia, there are around 65.6 million women and 43 million children exposed to cigarette smoke and thus act as passive smokers. If pregnant women act as passive smokers, then it can increase the risk of pregnancy complications, including LBW. Babies with LBW are one of the public health problems that must be considered because LBW is a major predictor of infant mortality, especially in the first month of life. The purpose of this study was to determine the effect of exposure to cigarette smoke on pregnant women as passive smokers on the incidence of LBW in Arjasa Health Center, Jember Regency. This type of research uses an observational analytic method with a retrospective case control study design. The sample of this study amounted to 60 people. The bivariate analysis using the chi square test stated that there was a significant relationship between exposure to 2x3 cigarette smoke (p = 0.031), exposure to 2x2 cigarette smoke (p = 0.030; OR = 4) and age of pregnant women (p = 0.033; OR = 5.2) with birth weight at Arjasa Community Health Center, Jember Regency. While the results of bivariate analysis using the chi square test stated that there was no significant relationship between jobs (p = 0.422; OR = 1.78), history of parity (0.784; OR = 1.3), and ANC frequency (p = 1,000; OR = 1.17). the results of multiple logistic regression analysis revealed that there was a significant effect between exposure to cigarette smoke (p = 0.050; OR = 3.39) and age (p = 0.037; OR = 4.6) on birth weight at Arjasa Health Center, Jember Regency. The conclusion of this study is that exposure to cigarette smoke has a significant relationship with birth weight and age is the most influential risk factor for birth weight in Arjasa Health Center, Jember Regency. Keywords: Birth weight, LBW, cigarette smoke exposure